Debates in Indian philosophy : classical, colonial, and contemporary - Raghuramaraju, A. (New Delhi : Oxford University Press, 2006)
With special reference to modern period.
Includes bibliographical references (p. [125]-133) and index.
Keywords: PHILOSOPHY